2022
DOI: 10.3389/fmicb.2022.825413
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of a Novel CXCL10 mRNA Release Assay for Mycobacterium tuberculosis Infection

Abstract: One-fourth of the world’s population has been infected with Mycobacterium tuberculosis (M.tb). Although interferon-gamma release assays (IGRAs) have been shown to be valid methods for identifying M.tb infection and auxiliary methods for diagnosis of active tuberculosis (TB), lower sensitivity and higher indeterminate rate were often detected among immunosuppressed patients. IP-10 was an alternative biomarker due to the higher expression level after M.tb antigen stimulation, but whether CXCL10 mRNA (the gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Although this study did not investigate the performance when combining CXCL10 and IFNG mRNA, it demonstrated the benefit of combining suitable mRNA markers, such as IFNG, TNFα and IL-2R or TNFα, IL-2R, CXCL9, and CXCL10, to improve TB diagnosis and differentiate Mtb infection status [15]. On the other hand, Blauenfeldt et al [37] reported sensitivity and specificity for a CXCL10 mRNA assay of 80% and 98% [25]. Recently, Pan et al reported comparable performance for a molecular CXCL10 mRNA assay vs. T-Spot.TB in 352 patients with definite TB and 153 non-TB controls, with sensitivity of 93.9% vs. 94.5% and specificity of 98.0% vs. 100% for the diagnosis of Mtb infection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although this study did not investigate the performance when combining CXCL10 and IFNG mRNA, it demonstrated the benefit of combining suitable mRNA markers, such as IFNG, TNFα and IL-2R or TNFα, IL-2R, CXCL9, and CXCL10, to improve TB diagnosis and differentiate Mtb infection status [15]. On the other hand, Blauenfeldt et al [37] reported sensitivity and specificity for a CXCL10 mRNA assay of 80% and 98% [25]. Recently, Pan et al reported comparable performance for a molecular CXCL10 mRNA assay vs. T-Spot.TB in 352 patients with definite TB and 153 non-TB controls, with sensitivity of 93.9% vs. 94.5% and specificity of 98.0% vs. 100% for the diagnosis of Mtb infection.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Pan et al reported comparable performance for a molecular CXCL10 mRNA assay vs. T-Spot.TB in 352 patients with definite TB and 153 non-TB controls, with sensitivity of 93.9% vs. 94.5% and specificity of 98.0% vs. 100% for the diagnosis of Mtb infection. However, in a subgroup of 14 TB patients with HIV co-infection, the molecular CXCL10 mRNA test showed a significantly higher positive rate (92.9%) than T-Spot.TB (61.5%; p = 0.029) [37]. Varying stimulation protocols, such as distinct stimulants or stimulation times, may explain the differences in the performance of the molecular tests described in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study has confirmed that the IP-10 mRNA can be effectively used as a target for the diagnosis of M.tb infection in HIV-infected individuals, as evidenced by its higher sensitivity and lower indeterminate rate of the detection (Pan et al, 2021;Pan et al, 2022). However, whether it can be used as an auxiliary method for diagnosis of TB, should also be validated in a larger cohort.…”
Section: Introductionmentioning
confidence: 79%
“…This multicenter, prospective study was performed across five hospitals in China, including the Shanghai Public Health Clinical Center (Eastern), the Beijing Chest Hospital (Eastern), the Beijing Youan Hospital (Eastern), the Gansu Provincial Infectious Disease Hospital (Western) and the Eighth Affiliated Hospital, Xinjiang Medical University (Western). According to the positive rate of IP-10 mRNA release assay (92.9%) and IGRA (61.5%) among HIVcoinfected patients in our previous study (Pan et al, 2022), we performed sample size calculation and the final minimum sample size of TB/HIV co-infected patients was 143. Therefore, we prospectively and continuously recruited the suspected HIV/TB co-infected patients from the five participating hospitals and ended when the HIV/TB co-infected patients in case group was enough, between May 2021 and May 2022.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation